HISTORIC FISHING RIGHTS AND THE EXCLUSIVE ECONOMIC ZONE - Bernard, Leonardo (UI Scholars Hub, 2021)
The exclusive economic zone (EEZ) regime under Part V of the LOS Convention grants coastal States the exclusive right to fisheries within 200 nautical miles (M) of their coasts. However, the EEZ seems to recognise the exclusive fishing rights of coastal States at the expense of historic fishing rights. Yet, is this an accurate reading of applicable law? Despite the fact that historic fishing rights are not expressly recognised in the LOS Convention, many States still claim these rights in areas beyond their EEZ. China, for example, has consistently made claims that it has historic rights over the fisheries resources within the nine-dashed line in the South China Sea. This article seeks to explore this issue, by analysing the relationship between the EEZ regime and historic fishing rights, and identifying the circumstances where historic fishing rights can exist alongside the EEZ regime. The article will also distinguish between historic waters and historic fishing rights; as well as discuss the practice of States and precedents of international courts and tribunals in relation to historic fishing rights.